'Unwanted' is My Name: Culture, Patriarchy and Gender Bias Surrounding the Nakusa Girls of Maharashtra. (April 2017) - Shijith, V.P.; Sekher, T.V.
This study tries to explore the shocking 'Nakusa' phenomenon in the Satara district of Maharashtra by analysing the factors responsible for discrimination against girl children. Many parents have named their daughters as 'Nakusa/Nakoshi' means 'unwanted' in local Marathi language, in the hope and under the superstition that the next child will be a boy. A survey of 'Nakusa' households was carried out in 2013 in the selected villages besides case studies of parents and their 'unwanted' daughters. Most 'Nakusas' were either third or fourth daughter of their parents. 'Nakusa' girls are experiencing discrimination and socio-psychological problems, and are the silent victims of the most visible and crudest form of gender bias still persisting. Women called 'Nakusa', who have suffered on account of their name all through their lives, will they ever want to have a daughter?